Effectiveness of e-learning portal from students' perspective: A structural equation model (SEM) approach. Issue 2 (17th June 2019) - Chopra, Gaurav; Madan, Pankaj; Jaisingh, Piyush; Bhaskar, Preeti
Abstract : Purpose: E-learning has become an increasingly prevalent learning approach in higher educational institutions due to the fast growth of internet technologies in India. This paper aims to mainly focus on evaluating the effectiveness of the e-learning experience from students' perceptive. Design/methodology/approach: "Survey" method has been used to collect the data with the help of a structured questionnaire from the students who have registered on COURSERA (www.coursera.org/ ) website for e-learning. The questionnaire consisted of two sections e-learning system and e-learning effectiveness. E-learning system included items related to system quality, information quality and service quality. E-learning effectiveness dimension included user satisfaction and net benefits. The items in this section were measured on a five-point Likert scale ranging from strongly disagrees to strongly agree. The data collected have been analyzed using the SPSS version 17.0 and AMOS version 21.0. Findings: Results show that system quality and service quality contribute more in e-learning system compared to information quality. Students perception may be that information available on the website may not be very useful as it's a one-way mode of communication. The researcher also found that the three dimensions (system quality, service quality and information quality) of e-learning system contributes to user satisfaction and net benefits. Students are satisfied with e-learning websites and intent to continue to use it in future as well. They also found it beneficial as it helps them in career growth and making them employable. Originality/value: This paper proposed a second-order model of e-learning system and a second-order model e-learning effectiveness. E-learning system has been defined by three first-order constructs: a system quality, service quality and information quality. E-learning effectiveness has been defined by two first-order constructs: a user satisfaction and net benefits. The predictability of the proposed model is high to explain the impact of e-learning system on e-learning effectiveness.